2019
DOI: 10.1016/j.finel.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A modal coordinate catenary model for the real-time simulation of the pantograph-catenary dynamic interaction

Abstract: The computational cost required to simulate the pantograph-catenary dynamic interaction can be a limiting factor in certain applications. Specifically, for Hardwarein-the-Loop (HIL) simulations, real-time capabilities of the software are imperative.In this paper a combination of a modal coordinate approach with an offline/online strategy to build a very efficient simulation strategy is proposed. This novel approach preserves the accuracy of the results, compared with those obtained by classical finite element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This new approach produced higher accuracy results compared to results obtained with conventional finite element strategies. Simulation results showed that the proposed method can be used to perform pantograph HIL tests [88]. In his study, Koyoma investigated faults caused by the wear of the pantograph contact strip and the upward movement of the pantograph.…”
Section: Solution Methods Used In Pantograph-catenary Systems According To the Type Of Faultmentioning
confidence: 99%
“…This new approach produced higher accuracy results compared to results obtained with conventional finite element strategies. Simulation results showed that the proposed method can be used to perform pantograph HIL tests [88]. In his study, Koyoma investigated faults caused by the wear of the pantograph contact strip and the upward movement of the pantograph.…”
Section: Solution Methods Used In Pantograph-catenary Systems According To the Type Of Faultmentioning
confidence: 99%
“…The hardware-in-the-loop technique has been widely developed to couple a mimic catenary and realistic pantograph [19], which provide more convincing measured results to analyse the pantograph behaviour. To improve the simulation efficiency, some simplifications are made based on the idea of moving mesh [20], [21] and linearisation [22] without affecting the simulation accuracy. Base on numerical models, the influence of some critical parameters, such as the tension [23], pantograph interval [24], and catenary geometry [25] on the interaction performance are analysed.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Under this circumstance, the relationship between the interval of double pantographs and the running speed can be expressed by Eq. (11).…”
Section: Mechanism Of Deterioration Of Trailing Pantograph Current Collection Qualitymentioning
confidence: 99%
“…The measurement data is also collected to validate the validity of numerical models [8]. In order to improve the computational efficiency, the moving mesh method [9], [10] and modal coordinate model [11] are widely used. The importance of damping to improve to structural performance has been widely acknowledged [12].…”
Section: Introductionmentioning
confidence: 99%